Efficient synthesis of azetidine-2,3-diones from L-(+)-diethyl tartrate - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synlett, 2007)
A convenient route to enantiopure azetidine-2,3-diones is described. The chiral ketene generated from commercially available L-(+)-diethyl tartrate on Staudinger cycloaddition with different imines gave spiro-beta-lactams in good yields. These spiro-beta-lactams were transformed into azetidine-2,3-diones in excellent yields in a two-step process.
Keywords: Cycloaddition; imines; lactams; spiro compounds; stereoselective synthesis

Stereoselective synthesis of spiro-beta-lactams using D-(+)-glucose derived chiral pool: remarkable influence of the torquoelectronic effect - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron, 2007)
Diastereoselective synthesis of spiro-beta-lactams via [2+2] cycloaddition reaction of imines and chiral ketenes is described. The chiral ketene was prepared from commercially available, inexpensive D-glucose. Although, theoretically four diastereomers are possible, the reaction yielded only two diastereomers stereoselectively in good to moderate yields. The stereochemical outcome of the reaction was in accordance with the torquoelectronic model. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: imines; ketenes; spiro-beta-lactams; Staudinger reaction; stereoselective synthesis

Efficient formal synthesis of (S)-dapoxetine from enantiopure 3-hydroxy azetidin-2-one - Chincholkar, Pinak M.; Kale, Ajaykumar S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2009)
An efficient formal synthesis of S-(+) dapoxetine starting from 3-hydroxy azetidin-2-one is described. The intermediate (S)-3-(dimethyl amino)-3-phenylpropan-1-ol was synthesized in enantiopure form starting with 3-hydroxy azetidin-2-one in seven steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Azetidin 2 ones; beta-Lactams; Enantioselective synthesis; reduction; Staudinger reaction